STUDI DAN EVALUASI KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN KADNIUM (Cd) DI AIR DAN SEDIMEN PADA PERAIRAN SUNGAI KOTA TARAKAN - Darmiah dan; Ratno Achyani (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2015)
The purpose of research is to determine the content of heavy metals Pb and Cd in river waters Tarakan City. Water sampling method are using a van Dorn water sampler and sediment samples using egmen grabs. The sample extraction method by Kaushik (2009). Sampling locations are 9 rivers is Istra Buntu, Tg. Batu, Skip kampong 1, KKHM, Karang anyar, Juata laut, Juata korpri, Binalatung dan Pasar Batu. The results show the mean Pb in the water at all stations from 0.228 to 0.181 mg/L, while the average sediment from 0.280 to 0.180 mg/L. Cd levels in water averages 0.259 to 0.226 mg/L, while the average level of Cd in sediments from 0.257 to 0.233 mg/L. Evaluation of heavy metals Pb and Cd in the water at all observation station still is above the threshold of water quality standards and the sediment is below the required quality standards. Keywords : Sediments, Water, Status, Evaluation, Tarakan City River